NATALIA KOBRYNSKA IN OLHA DUCHYMINSKA’S MEMOIRS - Пахомов, В. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The image of writer and feminist Nataliia Kobrynska based on the memories of writer Olha Duchyminska is described in the article.